2019
DOI: 10.1080/21691401.2019.1640229
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long non-coding RNA CCAT2 acts as an oncogene in osteosarcoma through regulation of miR-200b/VEGF

Abstract: Background/aim: Colon cancer-associated transcript 2 (CCAT2) is a new lncRNA, which is closely associated with risk of several cancers. The aim of this study was to explore the regulatory mechanism of CCAT2 in osteosarcoma (OSA). Methods: Cells were transfected with si-CCAT2, microRNA (miR)-200b inhibitor and the corresponding controls. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to measure the expression of CCAT2 and miR-200b in OSA tissues and cell lines. CCK8 and bromodeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…[23][24][25] VEGF was also manifested to implicate in the progression of several tumors, such as laryngeal cancer and osteosarcoma, through modulation of cancer cell proliferation, invasion and migration. 7,26 Inhibitors of VEGF and VEGF receptor were illuminated to function as promising therapeutic options for renal cell carcinoma and glioblastoma. 27,28 Previous researches described that high level of VEGF predicted poor prognosis in ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] VEGF was also manifested to implicate in the progression of several tumors, such as laryngeal cancer and osteosarcoma, through modulation of cancer cell proliferation, invasion and migration. 7,26 Inhibitors of VEGF and VEGF receptor were illuminated to function as promising therapeutic options for renal cell carcinoma and glioblastoma. 27,28 Previous researches described that high level of VEGF predicted poor prognosis in ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Emerging evidence has demonstrated that VEGF is tightly relevant to tumor cell proliferation, invasion, migration and apoptosis in multiple human cancers, including osteosarcoma and hepatocellular carcinoma. 7,8 Moreover, a recent document manifested that VEGF depletion induced by microRNA-(miR)-377 hindered tumor angiogenesis in ESCC, and thus weakened ESCC progression, highlighting its role as a potential molecular target for ESCC treatment. 9 Panax notoginseng saponins (PNS) are the key active components isolated from the root of Panax notoginseng (Burk.)…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Nevertheless, the regulation of ARHGAP4 in pancreatic cancer is still undiscovered microRNAs (miRNA) are small endogenous non-coding RNA molecules with a length of about 18-25 nucleotides that repress protein translation through binding to the 3ʹ-untranlated region (UTR) of their target mRNA and are significantly involved in various cancers, including pancreatic cancer. [14][15][16] High expression of miR-196a, miR-27a, miR-221, miR-143, miR-135b, miR-199b-5p and miR-21, but low expression of miR-744, miR-455-3p and miR-655, in pancreatic cancer samples were found compared with normal samples and associated with poor prognosis. 17 In addition, the expression profile of miRNAs varies even in the different locations, 18 which further confirms that miRNAs have high application value in the diagnosis, prognosis evaluation and treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear enriched abundant transcript 1 (NEAT1) is a lncRNA transcribed from the diverse endocrinal neoplasia locus [10]. The interaction of lncRNA NEAT1 has been documented in glioma, prostate cancer and lung adenocarcinoma [11][12][13].LncRNA NEAT1 was also suggested as a tumor promotor in OS by several studies [14][15][16].MicroRNAs (miRNAs) are tiny (~ 22 nucleotides) endogenous non-coding RNA molecules which act at the post-transcriptional level and regulate mRNA expression [17]. They are involved in multiple complicated cellular behaviors [18].…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are tiny (~ 22 nucleotides) endogenous non-coding RNA molecules which act at the post-transcriptional level and regulate mRNA expression [17]. They are involved in multiple complicated cellular behaviors [18].…”
mentioning
confidence: 99%